Transcription of the myxobacterial hemagglutinin gene is mediated by a sigma 54-like promoter and a cis-acting upstream regulatory region of DNA. - Romeo, J M (1991)
Myxobacterial hemagglutinin (MBHA) is a major developmentally induced protein that accumulates during the period of cellular aggregation of the fruiting bacterium Myxococcus xanthus. In this study, DNA sequences mediating the transcriptional regulation of mbhA have been identified. Examination of nucleotide sequences upstream of the start site for mbhA transcription has indicated a region of DNA that bears strong homology to the consensus sequence for promoters recognized by the sigma 54 holoenzyme form of RNA polymerase of Escherichia coli and other eubacteria. Deletion of this sequence completely abolished mbhA transcription. Additionally, a cis-acting DNA element, affecting the efficiency of mbhA transcription, has been mapped within a region of DNA 89 to 276 nucleotides upstream of the sigma 54-like sequence. Transposon insertions, mapping within the cis element, drastically reduced mbhA transcriptional activity. These observations suggest that transcription of mbhA requires a productive interaction between a form of RNA polymerase that recognizes a sigma 54-like sequence and a transcriptional activator that binds to DNA sequences upstream of the mbhA promoter.